Complete F-type mitochondrial genome of freshwater mussels Unio douglasiae. (1st November 2016) - Wang, Guiling; Xue, Ting; Chen, Meiling; Guo, Liping; Li, Jiale
Abstract: The complete F-type mitochondrial genome of Unio douglasiae is reported for the first time in this research. It is 15, 767 bp in size and contains 13 protein-coding genes, 22 tRNA genes, and 2 rRNA genes. Except for COI, ND2, CYTB, ND1, ND6, ND4L, ATP8 with ATA start codon, and ND4 with ATT start codon, the remaining protein-coding genes initiate with the orthodox ATG start codon. There are 25 noncoding regions found throughout the mitogenome of Unio douglasiae, ranging in the size from 1 to 312 bp, the largest of which is between tRNA Glu and ND2 (312 bp).